Nawiązania do życia politycznego czasów stanisławowskich oraz idei filozoficzno-politycznych epoki oświecenia w twórczości teatralnej i parateatralnej Ignacego Potockiego - Śrama, Marcin (Studia Europaea Gnesnensia, 2024)
Ignacy Potocki was one of the foremost actors on the Polish political stage during the reign of Stanisław August Poniatowski, particularly during the Great Sejm. Among other things, he was a member of the Commission of National Education. He was also marginally occupied with literature, notably with playwriting. The aim of this paper is to discuss the dramatic oeuvre of Ignacy Potocki and interpret his works in terms of the ideological message they contain.